2015
DOI: 10.15446/acag.v64n4.44290
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta de Physalis peruviana a la fertilización con diferentes dosis de N, P y K en el Altiplano de Pasto, Colombia

Abstract: <p>En un Andisol Typic dystrandept del Altiplano de Pasto (2800 m.s.n.m., 12.6°C, 820 mm/año y 900 h de luz solar), Colombia, se evaluaron algunas variables de crecimiento, contenido de nutrientes y producción de uvilla (Physalis peruviana) como respuesta a la fertilización con N, P y K. Los tratamientos consistieron en la aplicación de urea (46% N) como fuente de N, superfosfato triple-SPT (46% de P2O5) como fuente de P y cloruro de potasio-KCl (60% K2O) como fuente de K, en dosis iguales para cada fuen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, Physalis fruits are marketed mainly by their weight; the T5 treatment presented plants with similar yield to those in T7, but with application of 75 % of the NPK used in the T7 treatment. Parra et al (2014) found positive effects of application of NPK on the yield of Physalis peruviana using rates of 560 mg dm -3 of N, 280 mg dm -3 of P 2 O 5 , and 720 mg dm -3 of K 2 O in an experiment conducted in Colombia.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Physalis fruits are marketed mainly by their weight; the T5 treatment presented plants with similar yield to those in T7, but with application of 75 % of the NPK used in the T7 treatment. Parra et al (2014) found positive effects of application of NPK on the yield of Physalis peruviana using rates of 560 mg dm -3 of N, 280 mg dm -3 of P 2 O 5 , and 720 mg dm -3 of K 2 O in an experiment conducted in Colombia.…”
Section: Resultsmentioning
confidence: 92%
“…Plants in T7 had higher shoot and total dry weights than those of the other treatments (TABLE 7). According to Parra et al (2014), the rates of 300 kg ha -1 of urea, 150 kg ha -1 of triple superphosphate, and 300 kg ha -1 of potassium chloride result in the highest plant height, dry weight, and NPK absorption. In the present work, the highest dry weight was found when using 1600 mg dm -3 of N, 4800 mg dm -3 P 2 O 5 , and 3200 mg dm -3 of K 2 O, corresponding to 400 kg ha -1 N, 1200 kg ha -1 P 2 O 5 , and 800 kg ha -1 of K 2 O, respectively.…”
Section: Resultsmentioning
confidence: 99%